2018
DOI: 10.1177/1753944718750338
|View full text |Cite
|
Sign up to set email alerts
|

Differential mRNA expression of inflammasome genes NLRP1 and NLRP3 in abdominal aneurysmal and occlusive aortic disease

Abstract: NLRP1 and NLRP3 inflammasomes might differentially mediate the chronic inflammatory response in abdominal aortic aneurysm (AAA) and aortic occlusive disease (AOD). We measure differential relative gene expression of NLRP1 and NLRP3 inflammasomes in aortic tissues from 30 patients undergoing AAA open repair compared to aortic biopsies from 30 patients undergoing surgery to treat AOD. Aortic wall samples from autopsy without aortic disease were used as controls. NLRP3 was overexpressed in patients with AAA and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Single-nucleotide polymorphisms in NLRP1 are associated with an increased risk of developing type-1 diabetes and systemic lupus erythematosus (SLE) in Brazilian population cohorts ( 113 ). Patients with aortic occlusive disease (AOD) have exhibited higher mRNA expression of NLRP1 than healthy individuals ( 153 ).…”
Section: Inflammasomes In Chronic Inflammatory Disordersmentioning
confidence: 99%
“…Single-nucleotide polymorphisms in NLRP1 are associated with an increased risk of developing type-1 diabetes and systemic lupus erythematosus (SLE) in Brazilian population cohorts ( 113 ). Patients with aortic occlusive disease (AOD) have exhibited higher mRNA expression of NLRP1 than healthy individuals ( 153 ).…”
Section: Inflammasomes In Chronic Inflammatory Disordersmentioning
confidence: 99%
“…2,23 Therefore, blocking or inhibiting the activation of NLRP3 may become a novel therapeutic target for ischemic cerebrovascular disease. 23 This data, Beclin1/NLRP3 signal pathway is a critical downstream effector of DAPK1 by ATP production. Oikonomou et al 24 showed that noncanonical fungal autophagy inhibits inflammation in response to IFN-γ via DAPK1/NLRP3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…33 With the progress of research, increasing evidence shows that inflammation plays an important role in the occurrence and development of TAAs. 6,22 As an indicator of systemic inflammation, LMR is also a routine and economical detection index for patients, which can provide a reference for the clinical treatment of patients to a certain extent. There are a few limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recent studies have shown that multiple inflammation-related factors are closely associated with the pathogenesis of TAAs. 5,6 The main pathological manifestations of TAA are continuous dilation of the artery caused by the invasion of inflammatory cells, destruction of the middle elastic protein matrix, inflammatory cell infiltration in the aortic wall, thrombosis in the lumen, and elevated C-reactive protein (CRP) levels. [7][8][9] In the progression of TAA, the expression of inflammatory cells within the aneurysmal wall increased and the serum proinflammatory cytokines were elevated.…”
Section: Introductionmentioning
confidence: 99%